Anti‐D immunoglobulin therapy for pediatric ITP: Before and after the FDA's black box warning. Issue 11 (27th June 2013) - Thompson, Joel C.; Klima, Jennifer; Despotovic, Jenny M.; O'Brien, Sarah H.
Abstract In March 2010, the Food and Drug Administration (FDA) issued a black box warning for anti‐D immunoglobulin (anti‐D), an approved treatment for immune thrombocytopenia (ITP). It is unknown if and how clinical practice at U.S children's hospitals has since changed. We sought to describe inpatient anti‐D usage, laboratory monitoring, and anti‐D complications before and after the FDA warning. Using the Pediatric Health Information System, we collected data from 41 children's hospitals. There was a modest but statistically significant decrease in anti‐D usage from pre‐warning to post‐warning. Severe complication rates were very low and did not change appreciably. Pediatr Blood Cancer 2013;60:E149–E151. © 2013 Wiley Periodicals, Inc.